Design innovation and network architecture for the future internet - Boucadair, Mohamed; Jacquenet, Christian (Advances in web technologies and engineering (AWTE) book series., 2021)
"This edited book offers a comprehensive overview on the recent advances in networking techniques that are likely to shape the future Internet and which also mitigate currently known issues of architecture, security and networking"--